Genetic and Epigenetic Constructs of Progressive Supranuclear Palsy. Issue 2 (April 2022) - Debnath, Monojit; Dey, Saikat; Sreenivas, Nikhitha; Pal, Pramod Kumar; Yadav, Ravi
Background: Progressive supranuclear palsy (PSP) is a rapidly progressive primary tauopathy characterized by vertical gaze palsy, postural instability, and mild dementia. PSP shows high clinical and pathologic heterogeneity. Although a few risk factors exist, such as advanced age and environmental toxins, the precise etiology remains largely elusive. Compelling evidence now suggests that genetic background plays a pivotal role in the pathogenetic pathways of PSP. Notably, PSP is genetically and phenotypically a complex disorder. Given the tau pathology, several studies in the past have identified microtubule-associated protein tau ( MAPT ) gene mutations/variations and its haplotype as the major genetic risk factor of PSP, both in the sporadic and the familial forms. Subsequently, genome-wide association studies (GWAS) also identified several novel risk variants. However, these genetic risk determinants fail to explain the pathogenetic basis of PSP and its phenotypic spectrum in majority of the cases. Some genetic variants are known to confer the risk, while others seem to act as modifier genes. Summary: Besides the complex genetic basis of PSP, the pathobiological mechanisms, differential diagnosis, and management of patients with PSP have further been complicated by genetic conditions that mimic the phenotypes of PSP. This is now becoming increasingly apparent that interactions between genetic and environmental factors significantly contribute to PSP development. Further, the effect of environmental factors seems to be mediated through epigenetic modifications. Key message: Herein, we provide a comprehensive overview of the genetic and epigenetic constructs of PSP and highlight the relevance of genetic and epigenetic findings in the pathobiology of PSP.